First trimester termination of pregnancy. (February 2020) - Lui, Man-Wa; Ho, Pak-Chung
Abstract: First trimester termination of pregnancy (TOP) is a safe and effective procedure. The complete abortion rates of surgical and medical abortion are approximately 97% and 95%, respectively. Vacuum aspiration (VA) either by electrical suction or manual aspiration is the method of choice for surgical TOP. Risk of significant bleeding is ≤ 5% in VA, while major complications occur in <1%. The risk of infection after VA can be reduced significantly by using prophylactic antibiotics or by the screen-and-treat strategy. Pre-operative administration of misoprostol can also reduce the risk of complications. The combination of 200 mg mifepristone followed by 800 μg misoprostol 24–48 h later is recommended for first trimester medical TOP. If mifepristone is not available, misoprostol can also be used alone, but repeated doses may be required and the complete abortion rate may be lower. Due to the reduced efficacy in more advanced gestation, repeated doses of misoprostol may be required for medical TOP over 9 weeks of gestation. The complete abortion rate with this regimen is 95% or more. Gastrointestinal upsets can occur in up to 50% of women, but major complications are rare. There was no lower limit of gestational week for TOP, although extra precaution is required for the confirmation of completion of procedures and exclusion of ectopic pregnancy. Highlights: Both surgical and medical methods of TOP in the first trimester are safe and effective with a complete abortion rate ≥ 95%. Either electric or manual aspiration is the preferred surgical method. Mifepristone followed by misoprostol is the most effective medical regimen. Misoprostol alone regimen can be considered if mifepristone is not available.